Investigation of optical and structural properties of three-dimensional InGaPAs islands formed by substitution of elements of the fifth group. (December 2020) - Andryushkin, V V; Gladyshev, A G; Babichev, A V; Kolodeznyi, E S; Novikov, I I; Karachinsky, L Ya; Nevedomskii, V N; Egorov, A Yu
Abstract: We propose a new method to obtain the three-dimensional quantum-sized object arrays with reduced surface density. These arrays are formed by elastic transformation of the InGaPAs layer grown on the GaAs surface. We present the results on influence of the InGaP layer thickness, the substrate temperature, and exposure time in the arsenic flow on the optical and structural properties of the formed three-dimensional islands.